Analisis Penerapan Etika dalam Pelayanan Klinis Terapis Wicara - Siswanto, Arif; Nugroho, Setyadi (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: In line with the increasing number of speech therapists, the potential for ethical violations is also greater. Speech therapists must be able to ensure the security, comfort and safety of their clients while receiving speech therapy services in their workplace consistently and avoid ethical problems. Currently, there are hundreds of speech therapists working in the ex-Karesidenan Surakarta area and working in various services such as hospitals, clinics, schools, and independent practices. Objectives: This study aims to find out how the application of ethics in clinical services of speech therapists in Surakarta. Methods: This study has a qualitative descriptive design. Results: The application of ethics to the beneficence element was mostly moderate (67.4%). The application of ethics to the Nonmaleficence element was mostly moderate (65.2%). The application of ethics to the autonomy element was predominantly in the high category (71.7%). The application of ethics to the justice element was mostly in the moderate category (78.3%). This study also found that educational level influences the application of ethics in clinical settings with (p = 0.045). Meanwhile, the gender variable (p = 0.599) and the workplace variable (p = 0.426) so that both did not influence ethical services in clinical settings. Conclusion: There is still a need for systematic efforts from all speech therapy stakeholders to continue to socialize clinical services that apply ethical principles to avoid clinical problems related to ethical issues in the future. Keywords: Ethics, Speech therapy services